SYSTEM SECURITY SYSTEM USING ROOM TYPE CARDLOCK AL5H - Elly Agustina Julisawati (JAKSTIK Journal, 2004)
With the flexibility of key electrical current, the current key system can be combined withhotel management system, so the hotel can easily modify the model code generation cardlockcombination. With the above considerations, the authors tried to simplify the front office or athotels and apartment buildings to make the process of "Room Security System usingCardlock System Type AL5H"